2018
DOI: 10.1002/acp.3489
|View full text |Cite
|
Sign up to set email alerts
|

Liar, liar: Consistent lying decreases belief in the truth

Abstract: This study investigated the effects of lying on belief ratings for autobiographical childhood events. Participants lied by trying to convince the experimenter that likely events had not happened and that unlikely events had happened. Participants consistently lied, consistently told the truth, and alternated lying and truth telling across two sessions. Results showed that consistent false assents increased belief in those false events and that consistent false denials decreased belief in those true events.Fals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…Recent experimentation has examined whether false denials might act as some form of internal feedback that may affect belief. Although in one of our studies, we did not find evidence for this (Otgaar et al, 2016), Polage (2019) recently found that repeated false denials decreased belief in the truth of events (see also Romeo et al, 2019).…”
Section: Potential Mechanisms Underlying Denial-induced Forgettingcontrasting
confidence: 80%
See 2 more Smart Citations
“…Recent experimentation has examined whether false denials might act as some form of internal feedback that may affect belief. Although in one of our studies, we did not find evidence for this (Otgaar et al, 2016), Polage (2019) recently found that repeated false denials decreased belief in the truth of events (see also Romeo et al, 2019).…”
Section: Potential Mechanisms Underlying Denial-induced Forgettingcontrasting
confidence: 80%
“…Specifically, the act of denial might make people less likely to believe that a certain event took place. Although Otgaar and colleagues (2016) did not find evidence for this, Polage (2019) recently showed that repeated denials of FALSE DENIALS AND FALSE MEMORY FORMATION 29 experiences made people decrease their belief in the occurrence of these experiences. Also, Romeo and colleagues (2019) recently showed that feigning memory loss -which can be seen as some form of denial-also reduced belief in the occurrence of an experienced event.…”
Section: False Denials and False Memory Formation 27mentioning
confidence: 98%
See 1 more Smart Citation
“…These deceptive strategies produce different memory outcomes that are also correspondingly placed along a continuum. On the one hand, research has shown that falsely denying certain event‐related details during an interview can eventually lead to forget that those details were previously denied (e.g., Otgaar, Howe, Smeets, & Wang, 2016; Otgaar, Romeo, Howe, & Ramakers, 2018; Polage, 2018). On the other hand, fabricating new information has been shown to increase memory error rates at a later stage (e.g., Van Oorsouw & Giesbrecht, 2008), although it does not seem to undermine the gist of correct recollection (e.g., Ackil & Zaragoza, 2011; Chroback & Zaragoza, 2008).…”
Section: Simulating Amnesia In the Memory And Deception Frameworkmentioning
confidence: 99%
“…For example, actors tend to omit facts when recalling a past transgression that highlights the severity of the transgression and their responsibility (Baumeister, Stillwell, & Wotman, 1990;Kearns & Fincham, 2005;Stillwell & Baumeister, 1997). They also tend to selectively recall facts so that prior lies seem closer to the truth (Colwell et al, 2011;Polage, 2017Polage, , 2019 and forget moral rules after engaging in acts that violate them (Shu & Gino, 2012;Shu et al, 2011). Of note, Kouchaki and Gino (2016) found that "unethical amnesia" triggered by earlier unethical action led actors to repeat such action subsequently.…”
Section: Cognitive-dissonance Perspectivementioning
confidence: 99%